Systemic regulation of nodule structure and assimilated carbon distribution by nitrate in soybean - Li, Sha; Wu, Chengbin; Liu, Hao; Lyu, Xiaochen; Xiao, Fengsheng; Zhao, Shuhong; Ma, Chunmei; Yan, Chao; Liu, Zhilei; Li, Hongyu; Wang, Xuelai; Gong, Zhenping (Frontiers in Plant Science, 2023)
The systemic effect of nitrate on nodule structure, function, and carbon distribution in soybean (Glycine max (L.) Merr.) was studied in a dual-root growth system, with both sides inoculated with rhizobia and only one side subjected to nitrate treatment for four days. The non-nodulating side was genetically devoid of the ability to form nodules. Nutrient solutions with nitrogen concentrations of 0, 100, and 200 mg L-1 were applied as KNO3 to the non-nodulating side, while the nodulating side received a nitrogen-free nutrient solution. Carbon partitioning in roots and nodules was monitored using 13C-labelled CO2. Other nodule responses were measured via the estimation of the nitrogenase activity and the microscopic observation of nodule ultrastructure. Elevated concentrations of nitrate applied on the non-nodulating side caused a decrease in the number of bacteroids, fusion of symbiosomes, enlargement of the peribacteroid spaces, and onset of degradation of poly-β-hydroxybutyrate granules, which is a form of carbon storage in bacteroids. These microscopic observations were associated with a strong decrease in the nitrogenase activity of nodules. Furthermore, our data demonstrate that the assimilated carbon is more likely to be allocated to the non-nodulating roots, as follows from the competition for carbon between the symbiotic and non-symbiotic sides of the dual-root system. We propose that there is no carbon competition between roots and nodules when they are indirectly supplied with nitrate, and that the reduction of carbon fluxes to nodules and roots on the nodulating side is the mechanism by which the plant systemically suppresses nodulation under nitrogen-replete conditions.